India: Towards the Millennium Development Goals - Nirupam Bajpai and Sangeeta Goyal (CGSD Working Paper No. 3, 2004)
India's performance vis--vis human development has been mixed in the last decade. A high and sustainable rate of economic growth in the post reform period has reduced the number of people below the poverty line. Literacy rates have not only continued their trend rise but there has been a decline in the absolute number of illiterates for the first time. Population health, however, remains an area of neglect. Health indicators, while recording improvements over time, point to alarmingly high rates of malnutrition and mortality, especially among women and children, and widespread lack of access to medical care. Literacy rates have shown remarkable improvement in India in the last decade, both for males and females. Total literacy rates increased from 52 percent in1991 to 66 percent in 2001, with male literacy rates increasing from 64 percent to 76 percent and female literacy rates increasing from 39 percent to 54 percent The most heartening aspect of India's educational stride forward is the improvements recorded by the educationally backward states, especially the state of Madhya Pradesh. While there has been secular improvement in most health indicators, India continues to perform inferiorly in terms of health. Infant mortality rates have fallen and life expectancy has been rising. Maternal and child health, on the other hand, remain areas of neglect and as a result maternal mortality rates remain high, there is pervasive under-nutrition amongchildren and women, and conditions of safe child birth elude large proportions of pregnant women. Kerala has stood apart from the Indian experience in both education and health, achieving social development levels that are close to those found in the rich developed countries. With vigorous public action accompanied by financial commitment determinedly focused on providing access to good education and health to every individual, Kerala boasts of high literacy rates of over 90 percent for both males and females, and the highest life expectancy and lowest infant mortality rates among all states of India. Moreover, the sex ratio in Kerala, unlike that for India as a whole and insharp contrast to those of the rich states of Punjab and Haryana, is quite favorable for women. The state of Madhya Pradesh, historically one of the most socially backward states in India, has made rapid strides in education in the last decade. Between 1991 and 2001, literacy rates in Madhya Pradesh have jumped more than 20 percent points, increasing from 44.6 percent in 1991 to 64.11 percent in 2001, recording the highest decadal increase in literacy among Indian states. Moreover, female literacy rates in Madhya Pradesh improved more than male literacy rates, increasing from 39.29 percentin 1991 to 54.16 percent in 2001. To pursue the goal of mass literacy, Madhya Pradesh established 26,000 new primary schools within a year (1997-1998), achieving universal access. The unique feature of the state's remarkable achievement has been the use of organizational support provided by village councils (Panchayats) to spread education to rural areas and to its large population of scheduled castes and tribes